Infertility as health problem in Peru - Roa Meggo, Ysis (2014)
Infertility is a disease of the reproductive system. In Peru it is not considered an important public health disease. At present Peruvian public health criteria are outdated and fail to address the concept of health and non-communicable diseases whose growth is remarkable. Therefore a new approach to public health from a preventive point of view is proposed and criteria are evaluated. After analysis it is concluded that infertility should be considered a disease of public health interest with a preventive approach.